Healthcare monitoring and data analysis using IoT : technologies and applications - Jain, Vishal, 1983-; Chatterjee, Jyotir Moy; Kumar, Pradeep; Kose, Utku, 1985- (Healthcare technologies, 2022)
This edited book covers big data analysis methods of patient data gained via IoT-enabled monitoring systems. The information gathered can be processed to aid clinicians with diagnoses, prognoses and interventions. This book is a great reference to those using, designing, modelling and analysing intelligent healthcare services.